Si può osare? - Mezzadri, Marco (Educazione Linguistica Language Education, 2013)
Between the end of 2011 and 2012 a research was conducted by the Laboratorio di Glottodidattica of the University of Parma on a sample of 111 secondary school students, who attended courses in Italian language for study purposes managed by qualified L2 teachers. The main purpose of the study was to verify the possibility of managing the passato remoto and the passive form by non-native students of Italian at an A2 and a B1 level of competence, starting from school-type texts (expository texts dealing with historical topics). The research stemmed from a premise in the morphosyntactic syllabus used in the University of Parma’s Italstudio certificate, the premise being that the study of the passive form and the passato remoto be done earlier than in similar reference frameworks, namely that the two forms be introduced at the A2 level in terms of comprehension and B1 in terms of production.